The Pengaruh Cash Flow, Modal Kerja, dan Pertumbuhan Penjualan terhadap Cash Holding, Perusahaan Consumer Non-Cyclicals - Astuti, Windi; Ariyani, Liza; Rahman, Rahman; Azhar, Ibnu (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to determine the influence of operating cash flow, net working capital, and sales growth on cash holding. The population in this study of non-cyclicals consumer sector companies on the IDX from 2019-2022. This type of research is quantitative with a research population of non-cyclicals consumer sector companies on the IDX from 2019-2022, totaling 125 companies. Sampel selection was determined by purposive sampling method, resulting in 47 companies that meet the criteria and are included in the sample. The type data used is secondary data, collected using statistical dataset methods. The data analysis techniques used consist of deskriptive statistical analysis tests, classical assumption test, multiple linear regression analysis test, and hypotesis tests. The research results show that partially the operating cash flow and net working capital variables have a significant positive effect on cash holding. While the sales growth do not effect cash holding. Simultaneously the variables operating cash flow, net working capital, and sales growth, have a joint effect on cash holding.